Adaptive algorithms for elimination of electromyographic noise in the signal of the electrocardiogram - Тулякова, Н.О.; Трофимчук, А.Н.; Стрижак, А.Е. (Radiotekhnika, 2017)
Adaptive filtering algorithms for removing electromyigraphic (EMG) noise from electrocardiographic signal (ECG) are considered. Statistical characteristics of suppressing noise, described by symmetric a-stable distribution that models EMG, are obtained for mean square error and signal-to-noise ratio using numerical simulations for test ECG signal, registered with a stampling rate of 500 Hz. It is shown that the proposed adaptive myriad filters provide a high quality of the EMG removal in the ECG with a possible realization of processing in real time.